2021
DOI: 10.15446/profile.v23n2.82765
|View full text |Cite
|
Sign up to set email alerts
|

Embracing Conceptualizations of English Language Teacher Education From a Complexity Perspective

Abstract: Current conceptualizations of foreign language teacher education fail to represent the complexity of such education. This reflection highlights the need to embrace English language teacher education from a complex perspective. To explain this position, we define complex systems and complexity principles through examples of interconnected components of teacher education. Then, we trace emergent conceptualizations from theory and governmental documents that resonate with a complexity perspective. We suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This finding suggests growing understandings of ILTE complexity. Underlying this, it is the appreciation of education, and particularly of ILTE, as a complex phenomenon, in the sense of Cochran-Smith et al's (2014) In line with this, the call is for more integrative views of ILTE to advance towards its improvement (Garcia & Rosado, 2021).…”
Section: Articles and Authorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests growing understandings of ILTE complexity. Underlying this, it is the appreciation of education, and particularly of ILTE, as a complex phenomenon, in the sense of Cochran-Smith et al's (2014) In line with this, the call is for more integrative views of ILTE to advance towards its improvement (Garcia & Rosado, 2021).…”
Section: Articles and Authorsmentioning
confidence: 99%
“…Inasmuch, scholars, governments, and international agencies have been exploring strategies to improve the quality of education (Brown & Wisby, 2020) and teacher education. Aligned with these ideas, authors such as Garcia and Rosado (2021) suggest that the integration of complex epistemologies into ILTE could generate knowledge, skills and understandings to help teacher educators and student teachers "face variant, diverse, unique, and intricate phenomena (Vaillant, 2007)" (Garcia & Rosado, 2021, p. 282). In this sense, these authors indicated that ILTE "Programs should, for instance, demonstrate in their designs how multiple factors interconnect to influence teachers' learning thus ultimately affecting teacher quality" (p.282) in order to achieve this purpose.…”
Section: Introductionmentioning
confidence: 99%